2002
DOI: 10.1002/polb.10147
|View full text |Cite
|
Sign up to set email alerts
|

Probing the molecular interactions in the diffusion of water through epoxy and epoxy–bismaleimide networks

Abstract: ABSTRACT:Fourier transform infrared spectroscopy in the near-infrared (NIR) frequency range was used to investigate the molecular interactions occurring between absorbed water molecules and networks based on a tetrafunctional epoxy resin. One of these networks was a typical formulation containing 4,4Ј-diamino diphenylsulfone as a hardener, and the other was a modified resin containing 4,4Ј-bismaleimide-diphenylmethane (BMI) as a coreactive monomer. Molecular spectroscopy analysis confirmed the existence of mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 25 publications
3
81
1
1
Order By: Relevance
“…8,30 Considering the influence of water storage in bond strength durability of resin cements luted to zirconia, it has been demonstrated that water sorption may cause cement hydrothermal degradation after storing. 35,39 In these studies, the shear bond strengths showed a significant decrease after thermocycling. Conventional bis-GMA based resin-luting cements did not demonstrate a durable long-term bond to high-strength ceramic materials when using silica coating or sandblasting.…”
Section: Discussionmentioning
confidence: 94%
“…8,30 Considering the influence of water storage in bond strength durability of resin cements luted to zirconia, it has been demonstrated that water sorption may cause cement hydrothermal degradation after storing. 35,39 In these studies, the shear bond strengths showed a significant decrease after thermocycling. Conventional bis-GMA based resin-luting cements did not demonstrate a durable long-term bond to high-strength ceramic materials when using silica coating or sandblasting.…”
Section: Discussionmentioning
confidence: 94%
“…Previous work has shown that most aerospace composites show either a drop in the tan d peak with moisture absorption or sometimes multiple peaks; this depends on the test frequency. 11,12 At all frequencies, the DMA plots showed small but significant changes in the tan d peak position at the surfaces of the composite versus that of the center. This change in tan d may be due to oxidation stiffening of the surface layers; however, the change is small because such a thin layer has been affected.…”
Section: Composite Physical Changesmentioning
confidence: 94%
“…The 100-Hz plot showed a much broader and flatter peak at the surface, which may indicate a start of the double peak often shown in high-humidity-aged samples. 11,12 Another common result of accelerated aging testing of composites under high-humidity and spiking conditions that is also thought to occur in real environmental situations is surface microcracking. 10,11,13 A microscopic examination of the unpainted surface Figure 4 Differential spectrum between the surface and center of the composite plaque (see Fig.…”
Section: Composite Physical Changesmentioning
confidence: 99%
“…Because of this plasticizing effect, the water induces swelling and causes dimensional changes in the copolymer network. 4 The sorbed water may also induce chemical oxidation and hydrolysis of copolymer chains. 5 It has been found that the modulus of elasticity 6 and the mechanical strength 7 of copolymers are reduced after storage in water, and this reduction is increased with the hydrophilicity of the copolymer.…”
Section: Introductionmentioning
confidence: 99%